Role of noncoding RNAs in cardiac ageing - Varghese, Lijo N.; Schwenke, Daryl O.; Katare, Rajesh (Frontiers in Cardiovascular Medicine, 2023)
The global population is estimated to reach 9.8 billion by 2050, of which 2.1 billion will comprise individuals above 60 years of age. As the number of elderly is estimated to double from 2017, it is a victory of the modern healthcare system but also worrisome as ageing, and the onset of chronic disease are correlated. Among other chronic conditions, cardiovascular diseases (CVDs) are the leading cause of death in the aged population. While the underlying cause of the age-associated development of CVDs is not fully understood, studies indicate the role of non-coding RNAs such as microRNAs (miRNAs) and long noncoding RNAs (lnc-RNAs) in the development of age-associated CVDs. miRNAs and lnc-RNAs are non-coding RNAs which control gene expression at the post-transcriptional level. The expression of specific miRNAs and lnc-RNAs are reportedly dysregulated with age, leading to cardiovascular system changes and ultimately causing CVDs. Since miRNAs and lnc-RNAs play several vital roles in maintaining the normal functioning of the cardiovascular system, they are also being explored for their therapeutic potential as a treatment for CVDs. This review will first explore the pathophysiological changes associated with ageing. Next, we will review the known mechanisms underlying the development of CVD in ageing with a specific focus on miRNA and lnc-RNAs. Finally, we will discuss the therapeutic options and future challenges towards healthy cardiac ageing. With the global ageing population on the rise, this review will provide a fundamental understanding of some of the underlying molecular mechanisms of cardiac ageing.